2010
DOI: 10.1111/j.1365-2141.2009.07995.x
|View full text |Cite
|
Sign up to set email alerts
|

Complement activation on platelets correlates with a decrease in circulating immature platelets in patients with immune thrombocytopenic purpura

Abstract: The role of the complement system in immune thrombocytopenic purpura (ITP) is not well defined. We examined plasma from 79 patients with ITP, 50 healthy volunteers, and 25 patients with non-immune mediated thrombocytopenia, to investigate their complement activation/fixation capacity (CAC) on immobilized heterologous platelets. Enhanced CAC was found in 46 plasma samples (59%) from patients with ITP, but no samples from patients with non-immune mediated thrombocytopenia. Plasma from healthy volunteers was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
80
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 30 publications
1
80
0
1
Order By: Relevance
“…Increasing evidence suggests a role for complement activation in ITP (Peerschke, et al 2009, Najaoui, et al 2011). Although early work by Frank et al (1975) demonstrated that an intact classical complement pathway was required for damage of antibody sensitized mammalian cell membranes and the development of thrombocytopenia in a guinea pig model, the role for classical pathway (CP) complement activation in human ITP has not been definitively established.…”
mentioning
confidence: 99%
“…Increasing evidence suggests a role for complement activation in ITP (Peerschke, et al 2009, Najaoui, et al 2011). Although early work by Frank et al (1975) demonstrated that an intact classical complement pathway was required for damage of antibody sensitized mammalian cell membranes and the development of thrombocytopenia in a guinea pig model, the role for classical pathway (CP) complement activation in human ITP has not been definitively established.…”
mentioning
confidence: 99%
“…platelet antibodies the activation of the complement system has been shown to contribute to accelerated decrease in platelets by detection of the degradation components C1q or C4d in platelet-antibody complexes; 4 iii) in addition, in vitro stimulated T cells of some patients with ITP were able to trigger cytotoxic lysis of platelets by either CD3 + CD8 + T cells or CD56 + natural killer cells, 5 eventually in those patients in whom no circulating or plateletbound antibodies can be detected. Taken together, these data provide evidence that both T-and B-cell dependent processes are involved in the pathogenesis of ITP.…”
mentioning
confidence: 99%
“…The C1q downstream targets are platelets as well as intermediates in the thrombin cascades [32,33]. Soluble CR1 (sCR1) has been produced by recombinant technology and is being used in phase I human trials.…”
Section: Discussionmentioning
confidence: 99%